R&D-intensive SMEs in Europe: What do we know about them? - Raquel Ortega-Argilés; Lesley Potters; Peter Voigt (European Commission, Joint Research Centre (JRC), 2009)
The importance of SMEs in Europe's innovation process can be seen in both the academic and the political arena. Adopted in June 2008, the `Small Business Act' for Europe reflects the Commission's political will to recognise the central role of SMEs in the EU economy and was the first to put in place a comprehensive SME policy framework for the EU and its Member States. One of its main aims is to promote growth among SMEs by helping them to tackle problems that hamper their development. This kind of policy calls for a more in-depth look into the nature of the SME population in Europe. Several attempts have been made in recent years to draw taxonomies of firms, but mostly they do not control for size effects within the defined groups of firms. The purpose of this paper is to typify different groups of R&D-intensive SMEs distinguished according to their inputs into the innovation process. In particular, we draw attention to SMEs that contribute the most to the industrial R&D investment in the EU. To do so, we run a cluster analysis on a sample of top European R&D SME investors based on a unique dataset made up of the different waves of the European R&D Investment Scoreboard. The results show that several clusters of R&D-intensive SMEs can be defined by certain characteristics, but that the diversity between clusters calls for a more careful understanding before developing measures to support European R&D-intensive SMEs. For companies labelled as `corporate laboratories' according to the cluster analysis, it would be legitimate to question support for R&D, as these firms do not seem to have significant problems in finding investors that believe in their business model. On the other hand, e.g. the `Gazelles' do in fact grow, but struggle with the high capital investment needed to become and remain large. In this case, it seems it would be more effective to focus on the weaknesses (physical expansion) of these firms rather than supporting their strengths (knowledge, R&D).
Keywords: O33; 330; SMEs; innovation inputs; cluster analysis